Dionysus Meets the Caribbean: A Study of London Notting Hill Carnival in the Light of Samuel Selvon’s The Lonely Londoners - Saba, Anika (EAST WEST JOURNAL OF HUMANITIES, 2018)
Samuel Selvon’s iconic novel The Lonely Londoners (1956) captures the struggles of black Caribbean immigrants in the eponymous megacity. The setting of his novel is around the neighborhood of Notting Hill which has become synonymous with the Notting Hill Carnival that takes place in London every summer. This extravaganza, though has financial benefits for its participants, is an opportunity of social inclusion for the immigrants and subversion of British authority. This paper will trace the historical background of the London Notting Hill Carnival and the role of its main organizers, the Caribbean immigrants, in the light of Selvon’s novel which is based on fictional representations of this marginalized group. In doing so, the paper will refer to Richard Lehan’s argument of how the marginalized embody the Dionysian spirit in urban spaces, and Friedrich Nietzsche’s philosophical explanation of the age-old conflict between rationality and sensuality symbolized by the Apollonian and Dionysian myths in Western tradition. The purpose of this paper is to show how the black Caribbean immigrants of Selvon’s work embody the spirit of Dionysius in this modern-day Bacchanalia which takes place on the streets of London, and in extension, make an argument for the contribution of all marginalized immigrants in the repressed but vital spirit of Dionysus in the city.